Use of Pedicled Trapezius Myocutaneous Flap for Posterior Skull Reconstruction. Issue 6 (September 2015) - Singh, Mansher; Rios Diaz, Arturo J.; Cauley, Ryan; Smith, Timothy R.; Caterson, E.J.
Abstract : Background: Soft-tissue defects in posterior skull can be challenging for reconstruction. If related to tumor resection, these wound beds are generally irradiated and can be difficult from a recipient-vessel perspective for a free tissue transfer. Locoregional flaps might prove to be important reconstructive option in such patients. There is a very limited data on the usage of pedicled trapezius myocutaneous flaps for such defects. Methods: The authors reviewed existing study for usage of trapezius flap for posterior skull repair and used pedicled trapezius myocutaneous flaps based on the descending branch of superficial cervical artery (SCA) for reconstruction of posterior skull soft-tissue defect in an irradiated and infected wound. Results: Two patients were operated for trapezius myocutaneous flap for posterior skull defects complicated by cerebrospinal fluid (CSF) leakage and epidural abscess. There was no recipient or donor-site complication at a mean follow-up of 12.5 months. Neither of the 2 patients had any functional deficits for the entire duration of the follow-up. Although this flap was able to help in controlling the CSF leakage in the first patient, it successfully healed the cavity generated from epidural abscess drainage in the second patient. Conclusion: The large angle of rotation coupled with the ability to complete the procedure without repositioning the patients makes trapezius myocutaneous flap an attractive option for posterior skull reconstruction. In our limited experience, the pedicled trapezius flaps are a reliable alternative as they are well vascularized and able to obliterate the soft-tissue defect completely. The recipient site healed completely in infected as well as irradiated wound beds. In addition, the donor site can be primarily closed with minimal donor-associated complication.